Frankie's Kangaroo Caper - Lampard, Frank (Hachette Children's Group London, 2015)
Frankie and his team love playing football. There's always time for a game. And now that they have their magical football they're playing against teams they never imagined! This time the magic football takes them to Australia - what adventures will they find in the land Down Under?